Economic Determinants of Domestic Investment in an Oil-Based Economy: The Case of Iran (1965-2010) - Hadis Khonsary-Atighi (Copenhagen Business School (CBS), 2016)
The central focus of this thesis is the identification of theory-consistent economic determinants of aggregate and sectoral domestic investment in the context of the oil-rich and oil-based economy of Iran within the theoretical framework of modified neoclassical-accelerator type investment models. This thesis further attempts to extend this theoretically consistent framework by incorporating oil-driven financial constraint measures such as specified by cash flow models. The latter is justified on the basis of the presence of imperfect capital markets in Iran and the inherent uncertainty associated with the availability of oil-driven finance for investment due to the unpredictable nature of oil prices. A CVAR method is being employed to determine the theory-consistent long-run relationships between the variables of interest during 1974-2011. Motivated by the existing gaps in the investment and natural resource curse literature, the main objectives of the thesis include investigating: (i) the extent to which the theoretical framework is able to explain investment in the Iranian context and the underlying reasons for the (expected) partial applicability of such a framework; (ii) the relation between oil and investment patterns; and (iii) sectoral shifts during the process of capital accumulation and the role of the state in this process. Hence, the findings of this thesis contribute to current debates in the literature on the economics of natural resources and on investment, as well as to the application of the investment literature in the context of oil-abundant and -dependent economies like Iran. The empirical results, interestingly, showed that aggregate investment largely corresponds to factors which lie within the above theoretical framework. Notably, such a framework made it possible to make inferences and to draw policy implications based on the theoretically motivated long-run relationships between economic determinants of investment. It further allowed exploring how well such a framework, in the context of partial-market oil-driven economies like Iran, was applicable with some modifications that were needed to make the framework more appropriate for such economies.
hdl:10398/9456
Keywords: 650